Safety assessment of high doses of vaporized oxalic acid on honey bee worker health and queen quality - Tellarini Prieto, Emilio Enrique; Pietropaoli, Marco; Camus, Ylona; Polizel Camilli, Marcelo; Raza, Muhammad Fahim; Jose, Midhun Sebastian; Obshta, Oleksii; Bezerra da Silva, Marina Carla; Kozii, Ivanna; Moshynskyy, Igor; Edirithilake, Thanuri L.K.; Baril, Erin; et al. (Frontiers in Bee Science, 2024)
Introduction The honey bee ectoparasitic mite, Varroa destructor, is one of the main causes of honey bee colony loss worldwide. Synthetic acaricides are the most commonly used strategy for varroa control, however, resistance to these acaricides has emerged. Consequently, the use of organic acids for varroa control is gaining more interest among beekeepers. For example, oxalic acid (OA) is a natural compound that has been shown to be an effective acaricide against varroa mites, however, the potential toxicity of OA to adult bees and queens is poorly understood. The objective of the study was to evaluate the toxicity of incremental doses of vaporized OA on honey bee workers and queens. Methods We exposed 32 colonies to incremental doses (0, 5, 10 or 20 g per colony) of vaporized OA once per week over four consecutive weeks and we monitored the acute and long-term toxicity. We investigated the short-term effects of OA administration by evaluating adult bee mortality, brood production, and population size. Next, we evaluated the long-term effects of OA application on both worker bees and queens. Regarding workers, we investigated their ability to rear new queens. As for queens, we measured acceptance, performance, and sperm quality. Results We found that colonies treated with 20 g OA (20 times the label dose) had a statistically significant increase in worker bee mortality, with a non-significant, 23% decrease in brood relative to controls. No significant differences were observed in queen performance nor sperm quality. Discussion We found that repeated application of vaporized OA, at up to 20 times the label dose, had no significant short-term nor long-term, negative effects on colony or queen health, with the exception of a short-term increase in adult bee mortality in the 20 g OA-treated group. The results of this study support the safety of higher-than-label doses of OA for honey bee colonies. The observed increase in adult bee mortality in the 20 g OA dose group in this study suggests that OA doses should be maintained below 20 g per brood chamber.